Research on Optimized Design of In-Vessel Retention–External Reactor Vessel Cooling Strategy and Negative Effect Assessment - Chen, Peng; Wu, Zijie; Zhan, Dekui; Xia, Shaoxiong; Zhao, Xinhai (Frontiers in Energy Research, 2022)
Due to large uncertainty, the effectiveness of in-vessel retention (IVR) with external reactor vessel cooling (ERVC) for high-power reactors cannot be fully demonstrated during the transient process. To optimize the current IVR-ERVC strategy, the concept of IVR-ERVC with in-vessel injection (IVI) is studied. Two feasible IVI designs are proposed: 1) using the passive IVR water tank to implement simultaneous water injection in-vessel and ex-vessel and 2) using the passive severe accident dedicated in-vessel injection tanks (SADITs) to implement water injection in-vessel. The research on the feasibility and effectiveness of IVI is performed, and the corresponding negative effects are analyzed. The calculation results by using MIDAC show that the two proposed IVI concepts can greatly delay the accident progression in the core and reduce the decay heat peak of the molten pool in the lower head, thereby improving the effectiveness of the current IVR-ERVC strategy. And the negative effects are within acceptable ranges.